Effects of Cytochrome P450 2C19 Genetic Polymorphisms on Responses to Escitalopram and Levels of Brain-Derived Neurotrophic Factor in Patients With Panic Disorder. Issue 2 (March 2019) - He, Qianqian; Mei, Yan; Liu, Yuanyuan; Yuan, Zhuo; Zhang, Jian; Yan, Hong; Shen, Li; Zhang, Yong
Abstract: Purpose/Background: The purpose of this study was to examine the relationships between ytochrome P450 family 2 subfamily C member 19 ( CYP2C19 ) polymorphisms, brain-derived neurotrophic factor (BDNF) plasma levels, and treatment responses to escitalopram in Chinese patients with panic disorder (PD). Methods/Procedures: Ninety patients with PD were administered the Panic Disorder Severity Scale–Chinese Version (PDSS-CV) and Hamilton Anxiety Scale (HAMA-14) from baseline to 8 weeks. Escitalopram treatment (10 mg/d) was administered for 8 consecutive weeks. Three CYP2C19 metabolizers, including extensive metabolizers, intermediate metabolizers, and poor metabolizers (PMs), and 5 CYP2C19 genotypes were detected by polymerase chain reaction–genotyping microarray analysis. Baseline plasma BDNF levels were tested using human BDNF enzyme-linked immunosorbent assay kits. Findings/Results: Our findings showed no significant differences in demographic data, baseline PDSS-CV scores, or HAMA-14 scores between the 3 CYP2C19 metabolizer groups ( P 's > 0.05). Repeated-measures analysis showed a significant reduction in PDSS-CV ( F = 221.49, df = 3, P < 0.001) and HAMA-14 ( F = 260.47, df = 3, P < 0.001) scores over 8 weeks in PD patients. In addition, patients with PMs had a greater reduction in HAMA-14 scores ( F = 2.14, P = 0.049) than did those with extensive metabolizers and intermediate metabolizers. Moreover, our findings showed that patients with *2/*2 genotypes had a greater reduction in PDSS-CV scores than did those with other genotypes ( F = 2.14, df = 12, P = 0.015). Implications/Conclusions: Our study provides preliminary evidence of the effects of CYP2C19 PMs on treatment responses to escitalopram in Chinese PD patients, but no significant correlation between treatment responses and BDNF levels was found.